2013
DOI: 10.1177/0309132513481014
|View full text |Cite
|
Sign up to set email alerts
|

Sonic geographies

Abstract: Research into the geographies of sound and music has developed over the last 20 years, yet such work largely remains reliant on conventional verbal-textual methods of data collection and dissemination. In this paper we conduct a review of current approaches to sonic research, demonstrating that the erasure of audio media within geography silences a rich seam of empirical data. As a result, we propose that phonographic methods-including listening, audio recording, and playback-need to be developed further. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(36 citation statements)
references
References 64 publications
0
30
0
6
Order By: Relevance
“…To portray Dion's music and to understand its meanings and messages, discography and videography analysis (with English and French versions) helped with careful consideration of the messages that the artist has attempted to convey to her global audience. Therefore, phonographic methods through listening investigation, songs research and lyric analysis -as suggested by Carney (1998b), Gallagher and Prior (2014), Gallagher et al (2017) -provided important information. 7 This helped in understanding how this iconic music legend gained her unique international music stardom mirrored in the outstanding contribution of the artist to global popular music culture and in the musical meanings of her performances.…”
Section: Methodsmentioning
confidence: 99%
“…To portray Dion's music and to understand its meanings and messages, discography and videography analysis (with English and French versions) helped with careful consideration of the messages that the artist has attempted to convey to her global audience. Therefore, phonographic methods through listening investigation, songs research and lyric analysis -as suggested by Carney (1998b), Gallagher and Prior (2014), Gallagher et al (2017) -provided important information. 7 This helped in understanding how this iconic music legend gained her unique international music stardom mirrored in the outstanding contribution of the artist to global popular music culture and in the musical meanings of her performances.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, sound scholars have drawn from the theoretical possibilities of the feminist new materialisms (e.g., Thompson, 2017b). Concomitantly, a broader interest in the ontological turn has explored sound as affective (e.g., Clough, 2013;Gallagher, 2016;Gershon, 2013;Henriques, 2010;Thompson, 2017a;Thompson & Biddle, 2013); more-than-(e.g., Truman & Shannon, 2018) or nonrepresentational (e.g., Gallagher & Prior, 2014); in excess of, or more-than-, human (e.g., Scrimshaw, 2013); and as ontological vibration (e.g., Gershon, 2017;Goodman, 2010).…”
Section: Sound Studiesmentioning
confidence: 99%
“…He distinguished between cyclical natural rhythms and linear capitalist rhythms, arguing that the former have been progressively substituted by the latter with the aid of modern technologies. His views on the relation between rhythm and social structures have been criticized for its rigidity (Simpson 2008), yet some authors still found his insights on the relation between body, rhythm, and power valid (Edensor 2010;Tiwari 2010;Reid-Musson 2017). While Lefebvre's writings seem to have had a considerable impact on geographies of sound shortly after his work was translated into English (e.g.…”
Section: Geography Listens To Everythingmentioning
confidence: 99%
“…Since Rodaway's discussion, the term 'sonic geography' seems to have become more common in the Anglophone community (e.g. Matless 2005;Boland 2010;Boyd & Duffy 2012;Gallagher & Prior 2014), but the term 'listening geographies' also emerged (Gallagher et al 2017), meaning roughly the same as what Rodaway meant by aural geographies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation